Antibacterial Activity Of Mollusc Symbiotic Bacteria From Mangrove Ecosystem In Jepara Against S. aureus, V. harveyi and V. alginolyticus - Devi Oktavia Anjani; Barra Muzaffar Widayat; Otniel Kaleb Henry Sugiarto; Sunelsya Surya; Askiya Intan Suryani; Wilis Ari Setyati (Jurnal Moluska Indonesia, 2022)
Vibriosis is a shrimp disease caused by Vibrio sp. and become an obstacle for shrimp farmer because it mass mortality in shrimp. On the other hand, mangrove ecosystem has a high biodiversity of biota, one of which is Gastropods, which are rich in unique symbiotic bacteria due to their filter feeding habits. The symbiont bacteria from Gastropods are assumed to be capable of being a source of bioactive materials with antimicrobial, cytotoxic, and antineoplastic activities that can be utilized in the fields of marine biotechnology and marine pharmacy. This study aims to determine the antibacterial activity of the Gastropod symbiont bacteria against Vibrio harveyi, Vibrio alginolyticus, and S. aureus. Antibacterial activity was tested by paper disc diffusion method using Gastropod symbiont bacteria isolate on Mueller Hinton Agar media with pathogen target Vibrio harveyi, Vibrio alginolyticus dan S. aureus. The isolate liquid culture was dripped on paper discs on MHA media which had previously been inoculated with pathogen target. Observation of the inhibition zone was carried out in a period of 1x24, 2x24, and 3x24 hours. The results showed that there were 7 potential isolates with antibacterial activity against S. aures, V. harveyi, and V. alginolyticus, namely isolates BK.51, BK.54, BK.63, SK.52, SK.53, SK.54, and SK.61. The antibacterial activity of the seven isolates was more effective against V. harveyi and V. alginolyticus than against S. aureus. It can be concluded that the mollusc symbiont bacteria are potential as antivibirosis agents